2020
DOI: 10.1177/0008417420941975
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of Stroke Survivors’ Experience of Sensory Changes

Abstract: Background. Previous literature examined tactile and proprioceptive changes after stroke; however, the lived experience of changes in all sensory systems is still a gap in the literature. Purpose. To gain understanding of stroke survivors’ experience of sensory changes and how sensory changes impact participation in daily life activities. Method. This study utilized a qualitative description method. Researchers used semi-structured interviews with probing questions. Inductive content analysis approach was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 84 publications
0
14
0
Order By: Relevance
“…Even though the prevalence and severity of sensory hypersensitivity seem to decrease at a group level (Barker‐Collo et al, 2018; Shepherd et al, 2021), the evolution of sensory hypersensitivity also varies inter‐individually with some patients reporting earlier or greater alleviations of symptoms as compared to others (Alwawi et al, 2020; Truong et al, 2014). Truong et al (2014), for instance, reported that a reduction in light hypersensitivity was only present in 50% of their sample of 62 mTBI patients and that alleviation of light hypersensitivity was lower in patients who reported other comorbid post‐concussion symptoms (such as auditory hypersensitivity).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Even though the prevalence and severity of sensory hypersensitivity seem to decrease at a group level (Barker‐Collo et al, 2018; Shepherd et al, 2021), the evolution of sensory hypersensitivity also varies inter‐individually with some patients reporting earlier or greater alleviations of symptoms as compared to others (Alwawi et al, 2020; Truong et al, 2014). Truong et al (2014), for instance, reported that a reduction in light hypersensitivity was only present in 50% of their sample of 62 mTBI patients and that alleviation of light hypersensitivity was lower in patients who reported other comorbid post‐concussion symptoms (such as auditory hypersensitivity).…”
Section: Resultsmentioning
confidence: 99%
“…However, as illustrated in Figure 5, atypical sensory sensitivity is not limited to light or noise sensitivity but can extend across different modalities. Furthermore, the limited number of results regarding sensory sensitivity after stroke (Alwawi et al, 2020; Carlsson et al, 2004; Carlsson et al, 2009; Chung & Song, 2016; Wehling et al, 2015) or moderate to severe TBI (Goodrich et al, 2014; Knoll, Lubner, et al, 2020b) indicate that atypical sensory sensitivity is also prevalent after more severe brain injury. To date, there is no validated measure that is adapted to acquired brain injury that can be used in patients with severe cognitive disabilities, and can assess sensory sensitivity across all modalities (visual, auditory, tactile, gustatory, olfactory and vestibular).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations